2021
DOI: 10.1016/j.nano.2021.102374
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Mycobacterium tuberculosis antigen assembly into core-shell nanobeads for diagnosis of tuberculosis

Abstract: Despite recent advances in diagnosis, tuberculosis (TB) remains one of the ten leading causes of death worldwide. Here, we engineered Mycobacterium tuberculosis (Mtb) proteins (ESAT6, CFP10, and MTB7.7) to self-assemble into core-shell nanobeads for enhanced TB diagnosis.Respective purified Mtb antigen-coated polyester beads were characterized and their functionality in TB diagnosis was tested in whole blood cytokine release assays. Sensitivity and specificity were studied in 11 pulmonary TB patients (PTB) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…According to original and systematic analyses, good diagnostic performances are achieved only with multiple markers, 81. , 82. , 83.…”
Section: Biosensors For Tb Diagnosismentioning
confidence: 99%
“…According to original and systematic analyses, good diagnostic performances are achieved only with multiple markers, 81. , 82. , 83.…”
Section: Biosensors For Tb Diagnosismentioning
confidence: 99%
“…The Mtb-specific immune response showed that multiple cytokines, i.e., IFN-γ, IL-2, IL-6, IL-8, IP-10, MCP-1, MIP-1β, and TNF-α, were released when blood from patients with TB (cultured-confirmed) is stimulated with Mtb Ags (ESAT-6+CFP-10+TB7.7) [ 49 ]. Our team also demonstrated that the cytokine levels after the stimulation with fusion proteins of these Ags in coated polyester nanobeads could be used to differentiate PTB, TST + , and TST − healthy individuals by measuring the difference or ratio with unstimulated cytokine levels [ 116 ]. IL-2 and CCL11 were the best individual cytokines to differentiate between PTB and healthy individuals (TST + and TST − ) with a sensitivity and specificity of >80%, and the best combinations were IP-10+IL-2 and IFN-γ+IP-10+IL-2 with a sensitivity and specificity of >90%.…”
Section: Evaluation Of Host-derived Biomarkersmentioning
confidence: 99%
“…IL-2 and CCL11 were the best individual cytokines to differentiate between PTB and healthy individuals (TST + and TST − ) with a sensitivity and specificity of >80%, and the best combinations were IP-10+IL-2 and IFN-γ+IP-10+IL-2 with a sensitivity and specificity of >90%. These markers also had a similar sensitivity to differentiate between PTB and TBI (TST + ) [ 116 ]. Immunological profiles with multiple markers showed that IFN-γ, IP-10, IL-2, IL-6, CCL3, and CCL8 could not only be used as biomarker signatures for TBI, but also to elucidate the risk of reactivation [ 117 ].…”
Section: Evaluation Of Host-derived Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical field, nanoparticles cover different sectors, from diagnosis and to treatment of infectious and noninfectious diseases (Malekjahani et al, 2019;Noor et al, 2020;Sadani et al, 2020). For instance, diagnostic tools have used nanoparticles to detect specific molecules, whether they are proteins, DNA, or other markers of interest (Cinti et al, 2017;Rizzo et al, 2021;Sheffee et al, 2021;Vaquer et al, 2021) Thus, technological advances in nanoparticle production and development can lead to more efficient, low cost, and labelfree based medical devices (Gahlawat & Choudhury, 2019).…”
Section: Introductionmentioning
confidence: 99%